miR-10a-3p modulates adiposity and suppresses adipose inflammation through TGF-β1/Smad3 signaling pathway - Kiran, Sonia; Mandal, Mousumi; Rakib, Ahmed; Bajwa, Amandeep; Singh, Udai P. (Frontiers in Immunology, 2023)
Background: Obesity is a multifactorial disease characterized by an enhanced amount of fat and energy storage in adipose tissue (AT). Obesity appears to promote and maintain low-grade chronic inflammation by activating a subset of inflammatory T cells, macrophages, and other immune cells that infiltrate the AT. Maintenance of AT inflammation during obesity involves regulation by microRNAs (miRs), which also regulate the expression of genes implicated in adipocyte differentiation. This study aims to use ex vivo and in vitro approaches to evaluate the role and mechanism of miR-10a-3p in adipose inflammation and adipogenesis. Methods: Wild-type BL/6 mice were placed on normal (ND) and high-fat diet (HFD) for 12 weeks and their obesity phenotype, inflammatory gene, and miRs expression were examined in the AT. We also used differentiated 3T3-L1 adipocytes for mechanistic in vitro studies. Results: Microarray analysis allowed us to identify an altered set of miRs in the AT immune cells and Ingenuity pathway analysis (IPA) prediction demonstrated that miR-10a-3p expression was downregulated in AT immune cells in the HFD group as compared to ND. A molecular mimic of miR-10a-3p reduced expression of inflammatory M1 macrophages, cytokines, and chemokines, including transforming growth factor-beta 1 (TGF-β1), transcription factor Krüppel-like factor 4 (KLF-4), and interleukin 17F (IL-17F) and induced expression of forkhead box P3 (FoxP3) in the immune cells isolated from AT of HFD-fed mice as compared to ND. In differentiated 3T3-L1 adipocytes culture, the miR-10a-3p mimics also reduced expression of proinflammatory genes and lipid accumulation, which plays a role in the dysregulation of AT function. In these cells, overexpression of miR-10a-3p reduced the expression of TGF-β1, Smad3, CHOP-10, and fatty acid synthase (FASN), relative to the control scramble miRs. Conclusion: Our findings suggest that miR-10a-3p mimic mediates the TGF-β1/Smad3 signaling to improve metabolic markers and adipose inflammation. This study provides a new opportunity for the development of miR-10a-3p as a novel therapeutic for adipose inflammation, and its associated metabolic disorders.